Penanaman Modal Asing dalam Transisi Energi di Indonesia dan Tantangannya - Bobby Permana Putra (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Indonesia, as well as the global community, is striving to accelerate the energy transition, particularly through the development of New and Renewable Energy (NRE), to address environmental issues arising from climate change. However, the development of NRE is not an easy task; it requires comprehensive policy frameworks, regulatory support, and substantial long-term investment to achieve these goals. Based on research findings, the regulation of foreign direct investment is stipulated under Law No. 27 of 2007 concerning Investment, along with several regulations aimed at promoting the utilization of NRE as an energy source. Nevertheless, there remains no overarching legal framework that serves as the foundation for all policies related to NRE in Indonesia. Various challenges persist, particularly the need for stable and innovative long-term financing mechanisms to accelerate the country’s energy transition.